The relationship between Qualified Foreign Institutional Investors and stock return volatility： Evidence from China - Ｙｕｗｅｎ, Ｌｕ (2021)
In emerging economies such as India, Brazil, and Taiwan, the QFII (Qualified Foreign Institutional Investor) scheme has been frequently utilized as a transitional mechanism to promote progressive capital market liberalization. It was implemented in China in 2003 to attract more foreign value investors and long-term capital to the stock market, as well as to guide domestic investors to develop a more mature value investment philosophy, thereby stabilizing the market and facilitating a smooth stock market opening to the outside world. The main objective of this paper is to investigate whether the QFIIs influence stock market return volatility and, on this basis, to examine the direction of the effect. This study using EGARCH and VAR models to evaluate the proportion of QFII holdings and stock market return volatility as represented by the SCI300 from 2005 to 2020, with the proportion of domestic institutional investors' holdings added as a control variable. The results show that QFIIs are significantly associated with the volatility of China's stock returns and that changes in the percentage of QFII holdings increase volatility and the effect does not dissipate in the short term. The paper also finds that the participation of domestic institutional investors and stock market return volatility are also positively correlated, but the duration of the resulting shocks is shorter.